Nutrition determines outcome after severe burns - Berger, Mette M. (Annals of Translational Medicine, 2019)
Burns is one of the few human pathologies for which nutrition therapy has repeatedly been shown to contribute to both survival and recovery (1). This strong impact was again confirmed by Guo et al. in a study published in the May issue of the British Journal of Nutrition (2). Their amazing observation is particularly important due to severity of the burn injuries included in their large homogeneous cohort: the median burn size was 95% of body surface area (BSA), with 88% BSA being 3rd degree burns, while all patients suffered inhalation injury. Of note, a major burn is defined as an injury to more than 20% BSA in adults: in the present study, the entirety of the cohort qualifies for the appellation of “massive” burn injury.